Efficacy of iron chelates of lysine and glutamic acid as feed additive for all animal species - Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al. (EFSA journal, 2020)
Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the efficacy of iron chelates of lysine and glutamic acid (Iron‐LG) as nutritional feed additive for all animal species. The European Commission request followed an opinion of the FEEDAP Panel published in 2019; in that opinion the Panel could not conclude on the efficacy of the additive. The applicant submitted additional information to allow the FEEDAP Panel to complete its assessment; these additional data, related to the efficacy of the additive, are the subject of this opinion. Three studies were provided, one each with weaned piglets, pigs for fattening and laying hens. In the study in laying hens, improvements in iron content in egg yolk, iron in serum and in other iron‐related blood endpoints were observed. Based on the results of this study, the FEEDAP Panel concluded that the additive is a source of bioavailable iron, comparable to the standard inorganic iron source, and therefore, the additive is efficacious in meeting the animals’ requirements; the results of the study in pigs for fattening supported the bioavailability of Iron‐LG. The conclusion drawn by the Panel could be extrapolated to all animal species and categories.